Numerical experiments with an optimal power flow algorithm based on parametric techniques. - Lima, F.G.M.
This paper presents the results of numerical experiments with a new optimal power flow (OPF) algorithm based on a parametric technique. The approach consists of relaxing the original OPF problem by incorporating parametric terms to the objective function, the equality and inequality constraints. Such relaxation assures that any arbitrary initial solution, feasible or unfeasible, be the optimal solution of the OPF problem. As the scalar parameter changes, a family of OPF problems is created, whose necessary conditions are solved by Newton's method. An efficient strategy is proposed for updating the parameter and the optimal set of active inequality constraints of each intermediate problem. Two applications of the methodology are reported: the economic dispatch problem and the minimum transmission loss problem. These problems were solved for an 810-bus and a 2256-bus equivalent network of the South/Southeast interconnected Brazilian power system. The results show that the parametric approach is robust and efficient when applied to large-scale OPF problems
Keywords: 2256-bus equivalent network; 810-bus equivalent network; Newton's method; South/Southeast interconnected Brazilian power system; Economic dispatch; Equality constraints; Inequality constraints; Minimum transmission loss; Numerical experiments; Objective function; Optimal power flow algorithm; Parametric techniques; Scalar parameter changes; Updating active set